Avaliação das propriedades fotônicas do material fotoluminescente à base de SiO2 e Gd2O3 triplamente-dopado com Er3+/Yb3+/Eu3+ para conversão de energia - Rezende, Thaís Karine de Lima (2021)
This work reports the preparation, structural and spectroscopic characterization of the SiO2-Gd2O3:Er3+/Yb3+/Eu3+ materials. The materials were successfully obtained by the sol-gel method after heat treatment at 900 °C/ 8 h. The XRD and Rietveld refinement data indicated the formation of the cubic structure of Gd2O3 with spatial group Ia3 (206); the undoped sample also showed the formation of 8.24% of the monoclinic phase (C2/m). Infrared spectroscopy results confirmed the formation of SiO2 and Gd2O3 as well as the presence of dopants in the matrix. SEM micrographs indicated a system in which Gd2O3 are dispersed in SiO2. The EDS analysis showed peaks related to Si, Gd, O, in addition to Er, Yb and Eu, confirming the doping. The excitation spectra showed similar profiles, with bands assigned to transitions 8S7/2 → 6DJ and 8S7/2 → 6IJ of the Gd3+ ion, intraconfigurational 4f – 4f 5D0 → 7FJ (J: 0 – 4) of Eu3+ transitions and 4I15/2 → 4F7/2 of Er3+ ion, in addition to the O2-(2p) → Eu3+(4f6) charge transfer band. In the downconversion process, bands related to the transitions 5D0 → 7FJ (J: 0 – 4) of the Eu3+ ion, 2H11/2 → 4I15/2, 4S3/2 → 4I15/2 and 4F9/2 → 4I15/2 (Er3+) were observed. The 5D0 excited state lifetimes were calculated for all samples at different excitation wavelengths. The material SGEYE1 presented the highest lifetime value of 2.987 ms, suggesting that the tri-doped with Er3+, Yb3+ and 1.0 mol% of Eu3+ sample is the best concentration of Eu3+ for the SiO2-Gd2O3 system. In the upconversion process, bands were observed in all spectra related to 2H11/2 → 4I15/2, 4S3/2 → 4I15/2 and 4F9/2 → 4I15/2 transitions of Er3+ ion. Based on the best results of downconversion and upconversion, the SGEYE1 material was subjected to luminescence spectroscopy under simultaneous excitation at 247.50 and 980.00 nm. Both DC and UC phenomena were noted simultaneously with the presence of emission bands related to 5D0 → 7FJ (J: 0 – 4) transitions of Eu3+ ion, and 2H11/2 → 4I15/2, 4S3/2 → 4I15/2 and 4F9/2 → 4I15/2 transitions of Er3+ ion.